Current Situation and Factors Affecting the Musical Performance of Prospective Music Teachers - Cheng, Wenlin; Kirliauskienė, Rasa (Pedagogika, 2024)
Musical performance is the key content in the process of music education. Therefore, it is important for us to explore the current situation and factors affecting musical performance and further develop relevant skills for prospective music teachers. This study surveying 586 prospective music teachers using a questionnaire, the results indicate that physiological factors are the most important factors affecting musical performance, followed by psychological factors.